Peningkatan Mutu Pembelajaran Taman Pendidikan Al-Qur’an Melalui Metode Jāmiʻatī - Robingatun,; Sholichin, Riyadus; Khoirunnisa, Devi (TAAWUN, 2024)
This service aims to provide training to improve the quality of TPQ teachers to implement management and introduce the Jāmiʻatī Method. Having proper management of the education system also influences the quality of students. Where good management will create a learning system that is easy to understand, this research uses the Participatory Action Research (PAR) method. This research was carried out in a participatory manner among community members in a community. This PAR method uses three main pillars: research methodology, action dimension, and participation dimension. Implementing this method begins with preliminary mapping, building relationships with TPQ teachers, participatory mapping, formulating strategies, and launching actions. In this way, this research encourages transformative action results involving residents. The results of this mentoring produce an impact on the social relations of TPQ teachers on the importance of a learning method. The method given is the Jāmiʻatī Method which is given to the ustad/ustadzah in the form of TPQ learning exercises. Apart from that, understanding the importance of learning the Koran is also discussed in the form of socialization. This is so that parents are aware of the importance of Al-Qur'an education. After providing assistance with learning methods and socialization, this program is expected to be able to increase educational and management resources which are still unstructured.